Effect of cholesterol biosynthesis inhibitor on some biochemical parameters in normal male rats - M. S. Kalo (Iraqi Journal of Veterinary Sciences, 2009)
Endogenous cholesterol acts as a precursor of testosterone and other steroids hormones, this study was conducted to evaluate if there is a counterproductive effect associated with inhibition of cholesterol biosynthesis pathway specially in high doses and the degree of these effects in normal male rats. Forty eight adult Wistar rats divided into four groups, the first is control while the remaining three groups were treated with simvastatin (cholesterol biosynthesis inhibitor) in doses of 25, 50 and 100 mg.kg-1 respectively. Serum samples were observed at the baseline then every fifteen days while tissue samples were observed at day 30 and 60. Results of statistic refered to a significant decrease (p≤ 0.05) in serum total cholesterol and triglycerides (by 24 and 49% ± 3) respectively, also serum testosterone was significantly decreased (by 71% ± 2) in all groups compared to control after thirty and sixty days. The activity of alanine aminotransferase was increased (57% ± 3) versus to aspartate aminotransferase. Liver cholesterol was significantly decreased (by 72% ± 2) while testicular cholesterol was decreased except the group of 100 mg.kg-1 which in turns to elevate (61% ± 4), in addition also there was a decrease in body weight gain percentage neither the weights of liver nor testis was affected. In conclusion, the inhibition of denovo pathway of cholesterol biosynthesis negatively affects testosterone level in addition to cholesterol concentration in the tissues, body weight gain and alanine aminotransferase with no successful compensatory mechanism as related with testosterone level.